The Relationship Between Nutritional Status And Insulin-Like Growth Factor-1 Levels In Stunted Children In Cirebon Regency - Siti Pandanwangi; Akrom; Nurkhasanah; Zuniarto, Ahmad Azrul; Hidayati, Titiek; Tsai, Mei Ling (Window of Health : Jurnal Kesehatan, 2024)
Insulin-like Growth Factor-1 (IGF-1) is a growth hormone mediator that acts as a growth-promoting factor in the growth process and is also an indicator of the adaptive immune system. Children who experience stunting will experience obstacles to growth and cognitive and motor development, affecting their productivity as adults. This research aims to determine IGF-1 levels and their relationship with stunted children's nutritional status. The research method used was observational, with a cross-sectional research design. The population of stunted children in the Tegalwangi locus area, Cirebon Regency, a sample of children aged 24-60 months who met the inclusion criteria of not being disabled and not being sick, was 50 children. The research began with parents filling in informed consent. Continue to fill in data on date of birth, measure height and weight, take @1ml of the child's blood, and analyze IGF-1 using the ELISA method. The research results were that the average IGF-1 level for men was 16,812 ± 5,164 ng/ml and for women 13,810 ± 5,111 ng/ml. Average IGF-1 levels aged 24-36 months were 14,777 ± 4,742 ng/ml, 36–48 months 17,050 ± 4,280 ng/ml, and 48–60 months 15,214 ± 6,248 ng/ml. Data analysis using the Pearson correlation test obtained a value of p=0.871 based on age, p=0.047 based on gender, p=0.643 based on Height for age, and p=0.245 based on Weight for age (95% CI). The conclusion is that there is a relationship between the age of a stunted child and IGF-1 levels, and there is no relationship with nutritional status. All stunted children have IGF-1 values ​​below the standard value for normal children based on the literature, namely ≥ 28.54 ng/ml.